2021
DOI: 10.1101/2021.09.08.459397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of fish gut microbiota composition and holobiont’s metabolome by cyanobacterial blooms

Abstract: Background: Cyanobacterial blooms are one of the most common stress encountered by metazoans living in freshwater lentic systems such as lakes and ponds. Blooms reportedly impair fish health, notably through oxygen depletion and production of bioactive compounds including cyanotoxins. However, in the times of the microbiome revolution, it is surprising that so little is still known regarding the influence of blooms on fish microbiota. In this study, an experimental approach is used to demonstrate that blooms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 81 publications
4
17
0
Order By: Relevance
“…In our study system, it is possible that direct interactions exist between both bacterial community types considered here: Bacterioplankton transcriptional activity could affect the activity of bacterial members from the gill microbiome. For example, recent investigations suggested that the production of bioactive compounds, such as cyanotoxins produced by planktonic cyanobacterial strains, can significantly perturb fish microbiomes (Gallet et al . 2021; Duperron et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study system, it is possible that direct interactions exist between both bacterial community types considered here: Bacterioplankton transcriptional activity could affect the activity of bacterial members from the gill microbiome. For example, recent investigations suggested that the production of bioactive compounds, such as cyanotoxins produced by planktonic cyanobacterial strains, can significantly perturb fish microbiomes (Gallet et al . 2021; Duperron et al .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the selection of the bacterioplankton model based on Akaike scores gave a lot of weight to the parsimony criteria, thus advantaging simpler models (Bates et al 2015). Realistically, the global model was the one making the most sense biologically, as it included the influence of all the ecological, physico-chemical and geographical explicative variables considered in this study, which are known to affect the dynamics of host-associated microbiomes in many ecosystems (Goertz et al 2019;Sylvain et al 2020Sylvain et al , 2021Gallet et al 2021). It may seem surprising that the F ST values did not show a significant linear correlation with gill microbiome beta-diversity (Fig.…”
Section: The Host's Genetic Effectsmentioning
confidence: 99%
“…Fish were then exposed for 4 days to water, or water containing a strong but environmentally relevant density of the live non-axenic mono-clonal M. aeruginosa strain PMC 728.11 15 of the Paris Museum Collection 16 to simulate a bloom (100 µ g.L -1 Chl a ). The strain was cultured accordingly to anterior publication 11,14 (details in the supplementary information). M. aeruginosa concentrations were estimated after performing Chlorophyll a extractions and absorbance measurements as a proxy using a spectrophotometer 17 (Cary 60 UV-Vis, Agilent).…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical extraction (GLH850 OMNI; 25 000 r.min -1 ; 30s) followed by sonication (Sonics Vibra-Cell VCX 13; 60% amplitude; 30s) were performed on weighted samples suspended in the extraction solvent (75-25% UHPLC methanol-water, 1 mL per 100 mg of tissue or per 10 mg of lyophilized culture, on ice). After centrifugation (10 min; 4 °C; 15,300 g), gut pellets were dried and used for subsequent DNA extraction 14 .…”
Section: Metabolites Extraction and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation